Spray deposition and endoderiva on conilon coffee with different application rates - Côvre, Paola Ziviani; Freitas, Ismael; Locatelli, Tamara; Vitória, Edney Leandro da (Brazilian Journal of Production Engineering, 2020)
The application technology of agricultural pesticides is important in reducing losses to the soil and proper distribution and penetration in conilon coffee plants. The objective of this work was to analyze the deposition of the coffee leaf conilon and losses to the soil, provided by the pneumatic and hydropneumatic spray systems with different rates of application. The experiment was carried out in the municipality of Pinheiros, in the northern region of Espírito Santo, with geographical coordinates latitude 18º22’13 "south and longitude 40º12’48" west, in September 2017. Was conducted with five treatments distributed in a 5 x 3 factorial scheme, two sprays with different rates of application and three collection points of the deposit in the coffee tree (upper, middle and lower third of the height of the coffee plant). of deposit collection caused by runoff or soil losses, distributed in a randomized block scheme with four replications. Three leaves of each selected plant were collected, one in each third of the plant, all positioned at the median depth of the plant. To quantify the runoff of each, petri dishes were used below the canopy of the plant. Spraying with the use of the pneumatic sprayer has shown to be more uneven as to the deposition of the syrup in the plant canopy relative to the hydropneumatic sprayer.